El Teatro Como El Arte Que Posibilita a Los Estudiantes De Grado Quinto del Colegio Gimnasio Nuevo Suba Una Nueva Forma de Dar a Conocer e Interpretar su Entorno Escolar (2017)
This degree work constitutes the culmination of the Research process training of the master artist in training of the Bachelor's Degree in Art Education with emphasis in Dance and Theater - Faculty of Education of the Antonio Nariño University. Their developments, contributions, scope, questions and projections contribute to the growth of the Group of Didactic Research of the Performing Arts and is part of the Line that carries the same name.